Aging well in an aging society: physical health in older lesbian, gay, and bisexual adults - Baiocco, Roberto; Antoniucci, Chiara; Pistella, Jessica; Alessandri, Guido; Alivernini, Fabio; Borghi, Anna M.; Chirico, Andrea; Filosa, Lorenzo; Fini, Chiara; Palombi, Tommaso; Rosati, Fau; Tavolucci, Simone; et al. (Frontiers in Psychology, 2024)
Introduction. Older sexual minority people meet a double stigma in our society related to their sexual identity and chronological age. The present study explores how experiences of discrimination and prejudice, coming out, and personal resiliency influence physical health of older lesbian, gay, and bisexual (LGB) adults. Methods. Respondents were recruited through online advertisements and an online-based survey. The sample included 82 Italian cisgender LGB adults over 65 years: young older adults (65-70 years; 78%) and old-old adults (over 71 years; 22%). Regarding sexual orientation, the sample was composed of sexual minority women (n = 30; 37%) and sexual minority men (n = 52; 63%). Results. ANOVAs’ findings showed that sexual minority women described lower levels of physical health compared to sexual minority men. At the same time, old-old adults reported higher experiences of discrimination and prejudice compared to young older adults. Moreover, findings from hierarchical multiple regression analysis described that coming out, higher levels of personal resiliency, and fewer experiences of discrimination were predictors of physical health, regardless of age and sexual minority categories. Conclusion: These findings seem to align with previous studies that underline the relevance of investigating aging well in sexual minority people. Knowledge and awareness of LGBTQ+ issues are necessary for recognizing the unique needs and resources of older LGB people for promoting a healthy aging process.